Groundings in French and Indonesian narrative discourses: linguistic and culture analysis - Sajarwa (Humanities & Social Sciences Communications)
Abstract This study conducts a comparative analysis of grounding strategies employed in French and Indonesian narrative discourse. Utilizing both qualitative and quantitative methodologies, the research draws upon a corpus of French and Indonesian novels to examine the linguistic mechanisms utilized to establish grounding in these languages. This research questions the different markers of grounding in French and Indonesian narrative discourses, the types of grounding meanings, the role of culture in grounding, and what elements can strengthen grounding. The results of the textual analysis reveal that French employs the use of tenses, specifically the passé simple and imparfait (past tenses), to convey grounding, whereas Indonesian utilizes affixes, specifically the “me(N)-” and “di-” prefixes, for the same purpose. Further, the analysis illustrates that the “me(N)-” affix can be utilized to express both backgrounding and foregrounding, while the “di-” affix is restricted to foregrounding. Additionally, Indonesian also employs the use of third-person singular pronouns—“dia” and “ia”—to enhance grounding. The contextual analysis also highlights that in Indonesian narrative discourse, there is a tendency to repeat self-names as a form of politeness. This conclusion applies to languages that use tenses (e.g., French and English) as grounding markers and applies to languages that use affixes for grounding markers (e.g., Indonesian and Malay).